(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper studies the requirements to add efficiency in data mining. As the volume of data increases in tera bytes and that too remains distributed in nature , the data mining algorithms need to be adoptive to this trend. Scaling is one essential issue to be considered. Cloud gives a virtual platform for parallel and distributed processing. This paper analyses the scope for adding efficiency to association rule mining algorithms with cloud technology.In the present scenario as data are distributed in nature to mine them efficiently algorithms with distributed and parallel in nature are needed. Cloud environment supports distributed and parallel platform. Data privacy is still a very big problem to be addressed in cloud environment. This paper throws light on many encouraging aspects of cloud for data mining. Also it gives a study on adaptation of cloud environment for association rule mining